2020
DOI: 10.1021/acs.organomet.0c00343
|View full text |Cite
|
Sign up to set email alerts
|

Gold Complexes with ADAP Ligands: Effect of Bulkiness in Catalytic Carbene Transfer Reactions (ADAP = Alkoxydiaminophosphine)

Abstract: A family of gold(I) complexes of composition AuCl(ADAP) (ADAP = alkoxydiaminophosphine) has been prepared through a one-pot simple protocol in which the ADAP ligand is in situ prepared before reaction with the Au(I) source. Structural data demonstrate that these ADAP ligands exert a trans effect superior to those of phosphine or phosphite ligands. Evaluation of the buried volume (%V Bur ) indicates a steric hindrance higher than several NHC-, PR 3 or P(OR 3 ) ligands, in the context of AuCl(L) complexes. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…As a comparison, buried volumes of [(PR 3 )AuCl] complexes with R = t Bu, o Tol, and Mes are 38.1, 39.4, and 45.0%, respectively (2.28 Å, Au–P length). 21 Buried volumes of 45–53% have been reported for other gold(I) complexes bearing bulky alkoxydiaminophosphine 22 or acyclic diaminocarbene ligands. 23 …”
mentioning
confidence: 98%
See 1 more Smart Citation
“…As a comparison, buried volumes of [(PR 3 )AuCl] complexes with R = t Bu, o Tol, and Mes are 38.1, 39.4, and 45.0%, respectively (2.28 Å, Au–P length). 21 Buried volumes of 45–53% have been reported for other gold(I) complexes bearing bulky alkoxydiaminophosphine 22 or acyclic diaminocarbene ligands. 23 …”
mentioning
confidence: 98%
“…As a comparison, buried volumes of [(PR 3 )AuCl] complexes with R = tBu, oTol, and Mes are 38.1, 39.4, and 45.0%, respectively (2.28 Å, Au−P length). 21 Buried volumes of 45−53% have been reported for other gold(I) complexes bearing bulky alkoxydiaminophosphine 22 or acyclic diaminocarbene ligands. 23 To compare the reactivity of the new ferrocenyl phosphine gold(I) complexes with that of 1, 17 we studied the [4 + 2] cycloaddition of 1,6-arylenynes 7 (Scheme 3).…”
mentioning
confidence: 99%
“…Computational studies have revealed the crucial role of the arene group in the selectivity, explaining the large differences in comparison with the widely employed ethyl diazoacetate reagent. 13 We have recently described 12 the synthesis and characterization of a series of compounds of general formula (ADAP)AuCl, bearing alkoxydiaminophosphine ligands containing a five-membered ring that resembles that of NHC ligands. In view of our previous work with (NHC)AuCl compounds as precatalysts for carbene transfer reactions to C(sp 3 )−H and C(sp 2 )−H bonds 3,14,15 Regarding the functionalization of the C(sp 2 )−H bonds, both diazo compounds provide products derived from the formal insertion of the carbene group into such bonds; however, whereas EDA gives a mixture of the three o-, m-, and p-isomers, only the para isomer (2-p) is observed with PhEDA as the carbene precursor under the applied reaction conditions.…”
mentioning
confidence: 99%
“…In this contribution, we report the catalytic properties of a family of gold complexes containing alkoxydiaminophosphine ligands (ADAP) which promote the exclusive incorporation of carbene units into the C–H bond located at the para position of monosubstituted alkylbenzenes with the readily available ethyl 2-phenyldiazoacetate as the carbene source (Scheme d), not needing the elaboration on the diazo reagent. Computational studies have revealed the crucial role of the arene group in the selectivity, explaining the large differences in comparison with the widely employed ethyl diazoacetate reagent …”
mentioning
confidence: 99%
See 1 more Smart Citation